Impact of frailty on early rhythm control outcomes in older adults with atrial fibrillation: A nationwide cohort study - Yu, Ga-In; Kim, Daehoon; Sung, Jung-Hoon; Jang, Eunsun; Yu, Hee Tae; Kim, Tae-Hoon; Pak, Hui-Nam; Lee, Moon-Hyoung; Lip, Gregory Y. H.; Yang, Pil-Sung; Joung, Boyoung (Frontiers in Cardiovascular Medicine, 2023)
Purpose: Rhythm-control therapy administered early following the initial diagnosis of atrial fibrillation (AF) has superior cardiovascular outcomes compared to rate-control therapy. Frailty is a key factor in identifying older patients’ potential for improvement after rhythm-control therapy. This study evaluated whether frailty affects the outcome of early rhythm-control therapy in older patients with AF. Methods: From the Korean National Health Insurance Service database (2005–2015), we collected 20,611 populations aged ≥65 years undergoing rhythm- or rate-control therapy initiated within 1 year of AF diagnosis. participants were emulated by the EAST-AFNET4 trial, and stratified into non-frail, moderately-frail, and highly-frail groups based on the Hospital Frailty Risk Score. A composite outcome of cardiovascular-related mortality, myocardial infarction, hospitalization for heart failure, and ischemic stroke was compared between rhythm- and rate-control. Results: Early rhythm-control strategy showed a 14% lower risk of the primary composite outcome in the non-frail group (weighted incidence 7.3 vs. 8.6 per 100 person-years; hazard ratio [HR] 0.86, 95% confidence interval [CI] 0.79–0.93, p < 0.001) than rate-control strategy. A consistent trend toward a lower risk of early rhythm-control was observed in the moderately-frail (HR 0.91, 95% CI 0.81-1.02, p = 0.09) and highly-frail (HR 0.93, 95% CI 0.75-1.17, p = 0.55) groups. Conclusions: Although the degree attenuated with increasing frailty, the superiority of cardiovascular outcomes of early rhythm-control in AF treatment was maintained without increased risk for safety outcomes. An individualized approach is required on the benefits of early rhythm-control therapy in older patients with AF, regardless of their frailty status.